P376 Improving stress and fatigue in a real-world setting among patients with Inflammatory Bowel Disease through a digital platform. (27th May 2021) - Oddsson, S; Gunnarsdottir, T; Johannsdottir, L; Amundadottir, M; Frimannsdottir, A; Ylanne, K; Molander, P; Islind, A; Oskarsdottir, M; Thorgeirsson, T
Abstract: Background: Fatigue is one of the most prominent and disabling symptoms reported by adult patients with inflammatory bowel disease (IBD). Also, stress is perceived by these patients as one of the main causes of IBD flare-ups. Therapeutic guidelines call for effective disease assessment, early intervention, and personalized care using a treat-to-target approach which may be hard to achieve through standard care. Providing patients with effective self-management strategies and patient support programs (PSPs) via a digital platform to complement standard care, may be optimal for improving fatigue and reducing stress. The objective of this study was to perform a preliminary test of engagement and effectiveness of a newly developed 16-week PSP delivered via the digital platform Sidekick Health. Methods: Participants were recruited via Finnish IBD patient association websites and social media (advertisements through Facebook and Instagram). Participants entered baseline characteristics upon program signup. Platform engagement was automatically tracked, and participants reported stress, energy levels (fatigue), and quality of sleep through the platform. Results: An intention to treat (ITT) sample included 205 participants. Eighty people completed the required outcome measures during weeks 12-16 (completers). More women than men took part (61.5%) with the average age of 40.3 years (mean, SD=11.5) and average BMI of 27.9 (mean, SD=6.0). ITT analyses showed significant improvements in ratings of stress ( t (204)=3.488; p <0.01, percentage change=-9.52%), and energy levels ( t (204)=-2.381; p <0.05, percentage change=4.60%). No significant difference was observed in quality of sleep ( t (204)=-1.368; p =0.173). For completers (n=80), significant improvements were observed for stress ( t (79)=4.574; p <0.01, percentage change=-23.26%) and energy levels ( t (79)=-2.440; p <0.05, percentage change=9.48%) but not for quality of sleep ( t (79)=-1.319; p =0.191). Conclusion: These results indicate that participation in the Sidekick Health PSP for IBD has significant positive effects on patient-reported stress and energy levels. These findings are promising and provide initial support for using this digital platform for supplementing standard care for IBD patients.